Alternative scriptwriting : successfully breaking the rules. - Dancyger, Ken, ....-; Rush, Jeff, ....- (Amsterdam : Focal, 2007)
Alternative Scriptwriting 4E is an insightful and inspiring book on screenwriting concerned with challenging you to take creative risks with genre, tone, character, and structure. Concerned with exploring alternative approaches beyond the traditional three-act structure, Alternative Scriptwriting first defines conventional approach, suggests alternatives, then provides case studies. These contemporary examples and case studies demonstrate what works, what doesn't, and why. Because the film industry as well as the public demand greater and greater creativity, one must go beyond the traditional three-act restorative and predictable plot to test your limits and break new creative ground. Rather than teaching writing in a tired formulaic manner, this book elevates the subject and provides inspiration to reach new creative heights. Contents: Beyond the Rules; Structure; Critique of Restorative Three-Act Form; Counter Structure; Narrative and Anti-Narrative; Working with Genre 1; Working with Genre 2; Working Against Genre; Reframing the Active/Passive Character Distinction; Stretching the Limits of Character Identification; Main and Secondary Characters; Subtext, Action and Character; The Primacy of Character Over Action; The Subtleties and Implications of Screenplay Form; Character, History and Politics; Tone; Dramatic Voice/Narrative Voice; Digital Features; Writing the Narrative Voice; Rewriting; Adaptations from Contemporary Literature; Personal Scriptwriting: The Edge; Beyond the Edge
Keywords: Filmscenario's.; Schrijven -- Scenario's.